Toll like receptor-9 agonists stimulate prostate cancer invasion in vitro - Ilvesaro, Joanna M.; Merrell, Melinda A.; Swain, Telisha Millender; Davidson, Jennifer; Zayzafoon, Majd; Harris, Kevin W.; Selander, Katri S. (The Prostate, 2007)
BACKGROUND Toll‐like receptor 9 (TLR9) recognizes microbial DNA. In addition to immune cells, TLR9 expression has been detected in various cancer cells. We showed recently that TLR9 agonistic CpG‐oligonucleotides (CpG‐ODNs) induce matrix metalloproteinase‐13 (MMP‐13)‐mediated invasion in TLR9‐expressing (TLR9+) breast cancer cells. We investigated here TLR9 expression and function in human prostate cancer (CaP) cells. METHODS TLR9 expression was detected with Western blotting and immunohistochemistry. Invasion was studied with Matrigel‐assays. MMP‐13 was assayed with ELISA. RESULTS Human CaP cell lines and clinical samples exhibit various levels of TLR9 expression. Treatment of TLR9+, but not TLR9− CaP cells with CpG‐ODNs or bacterial DNA increased their invasion, which was inhibited with chloroquine. CpG‐ODN‐treatment also increased MMP‐13 activity and neutralizing anti‐MMP‐13 antibody prevented CpG‐ODN‐induced invasion in TLR9+ CaP cells. Estradiol up‐regulated TLR9 expression in LnCaP cells. CONCLUSIONS TLR9‐mediated invasion may represent a novel mechanism through which infections promote prostate cancer. Prostate 67: 774–781, 2007. © 2007 Wiley‐Liss, Inc.